ELF score ≥9.8 indicates advanced hepatic fibrosis and is influenced by age, steatosis and histological activity. (20th January 2015) - Fagan, Kevin J.; Pretorius, Carel J.; Horsfall, Leigh U.; Irvine, Katharine M.; Wilgen, Urs; Choi, Kihoon; Fletcher, Linda M.; Tate, Jill; Melino, Michelle; Nusrat, Sharmin; Miller, Gregory C.; Clouston, Andrew D.; et al.
Abstract Background & Aims There is increasing need to identify individuals with advanced liver fibrosis, who are at risk of complications such as hepatocellular carcinoma. The commercially available enhanced liver fibrosis (ELF) test provides a non‐invasive assessment of fibrosis severity. This study was designed to determine the diagnostic accuracy of the manufacturer's cut‐off value (≥9.8) in identifying advanced fibrosis. Methods The relationship between ELF score and fibrosis was examined using serum collected at time of liver biopsy for investigation of liver disease, particularly viral hepatitis. Fibrosis was staged using a modified METAVIR score. If available, liver tissue was recut and stained with Sirius red to determine collagen proportional area (CPA) and subsinusoidal fibrosis (SSF). Results Enhanced liver fibrosis score ≥9.8 had a sensitivity of 74.4% and specificity 92.4% for detecting advanced fibrosis. In the whole cohort (n = 329), ELF score was more likely to incorrectly classify individuals if age was ≥45 years and METAVIR inflammatory grade was 2 or 3 (adjusted OR, odds ratio 3.71 and 2.62 respectively). In contrast, ELF score was less likely to misclassify individuals in the presence of steatosis (OR 0.37). Neither SSF nor CPA explained the discordance in ELF score for patients with or without advanced fibrosis. Conclusion Although ELF score ≥9.8 reliably identifies advanced fibrosis in patients with chronic liver disease, both age and inflammatory activity need to be considered when interpreting the result. Importantly, ELF score performed well in the presence of steatosis and could thus be helpful in the assessment of fatty liver disease.